PUBLIC POLICIES DEVELOPMENT: CONVERGENCES AND DIVERGENCES IN THE BODOQUENA-PANTANAL GEOPARK - MARIA CRISTIANE FERNANDES DA SILVA LUNAS; ADEMIR KLEBER MORBECK DE OLIVEIRA; VERA LÚCIA RAMOS BONONI (Ambiente & Sociedade, 2016)
Abstract The Bodoquena-Pantanal Geopark was created by State edict in 2009, but its implementation and effective operation still depend on investments and actions. The public resources for investments are limited, and the private sector will invest if the State assures that the enterprise will be stable and profitable. This survey aims to analyze the convergences and divergences among public policies that occurs in the Geopark site. The method employed was the analysis by an adaptation of the MACTOR Method verifying implicit and explicit policies goals. The results indicate that most policies have common goals and are converging, although they are not always clear. In conclusion, the Geopark is a new demand for the government, that is linked to recurring and suppressed demands regarding regional development, and this policies converge among each other, if executed properly, can contribute to the Geopark implementation, which will act as a driving force to the regional development.